Implementation of Action Learning and Experiential Learning in Islamic Boarding Schools: A Systematic Literature Review - Al Husna; Uwes Anies Chaeruman; Maria Paristiowati (Proceeding of the International Conference on Global Education and Learning, 2025)
Islamic boarding schools (pesantren) as Islamic educational institutions face modernization challenges in developing effective learning methods. Action learning as an experience and reflection-based learning approach emerges as a relevant alternative. This article aims to conduct a systematic literature review on the implementation of action learning and experiential learning in Indonesian Islamic boarding school education. The research method uses a systematic literature review approach by analyzing 15 indexed journal articles from the 2018-2025 period. Inclusion criteria include articles in Indonesian and English, published in accredited journals, and discussing action learning or experiential learning in Islamic boarding schools. Analysis results reveal three main findings: (1) action research has been implemented to address specific problems such as student mental health with humanistic and participatory approaches, (2) experiential learning is applied through hadith learning, entrepreneurship programs, and life skills development that enhance cognitive abilities, communication, and student adaptation, (3) integration of action learning with pesantren values creates a distinctive learning model combining tradition and innovation. Identified research gaps include minimal longitudinal studies, lack of long-term impact measurement, and limited comparative analysis among pesantren. This study recommends developing a theoretical framework for action learning contextual to pesantren characteristics and further research with more comprehensive methodologies.